PERJANJIAN TIDAK TERTULIS DITINJAU DALAM SUDUT PANDANG HUKUM PERDATA - Ayu Puspita, Berliana Adinda; Marwiyah, Marwiyah (PSHPM Untag Semarang, 2024)
The existence of unwritten agreements is also based on the principle of freedom of contract, which gives parties the freedom to determine the type of agreement they will make. Traditional societies often use unwritten agreements in business transactions. In most cases, agreements between two parties are made in writing, with the rights and obligations of the parties clearly written down. If the agreement is not made in writing, or better known as an